2019
DOI: 10.1182/blood-2019-125989
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subpopulations and Expression of Immune Checkpoint Receptors PD-1 and Tim-3 in Patients with Chronic Myeloid Leukemia in a Discontinuation Trial

Abstract: Introduction: Immunological factors have been associated with deep molecular response (DMR) and treatment-free remission (TFR) in chronic myeloid leukemia (CML). Immune cell functions are restored in patients with DMR and this effect remains after TKI discontinuation. Recently, a multivariable model including CD4+ T cells, PD1+TIM3-CD8+ T cells and neutrophils counts showed ability to predict the likelihood of achieving molecular remission 4.0 (MR4) among other clinical parameters. In this prospective study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The immunological milieu at the time of TKI cessation plays a critical role in the success of TFR in CML. Several studies have found that natural killer (NK) cells are increased in TFR while immune suppressors, including regulatory T-cells (Tregs), are reduced [2][3][4][5] . Our group has previously demonstrated increased NK cells and concomitant decreased T-regs and monocytic myeloid-derived suppressor cells (MDSCs) at the time of TKI cessation in patients who achieved TFR compared with patients who relapsed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunological milieu at the time of TKI cessation plays a critical role in the success of TFR in CML. Several studies have found that natural killer (NK) cells are increased in TFR while immune suppressors, including regulatory T-cells (Tregs), are reduced [2][3][4][5] . Our group has previously demonstrated increased NK cells and concomitant decreased T-regs and monocytic myeloid-derived suppressor cells (MDSCs) at the time of TKI cessation in patients who achieved TFR compared with patients who relapsed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that natural killer (NK) cells are increased in TFR whereas immune suppressors, including regulatory T cells (T-regs), are reduced. 2 , 3 , 4 , 5 Our group has previously demonstrated increased count of NK cells and concomitant decreased count of T-regs and monocytic myeloid-derived suppressor cells (MDSCs) at the time of TKI cessation in patients who achieved TFR compared with patients who relapsed. We developed an immune effector-suppressor score calculated using absolute counts of NK cells, T-regs, and MDSCs, which predicted TFR outcomes with 85% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the clonogenic frequency and function of NK cells has been demonstrated in chronic-phase CML patients at the time of diagnosis, worsening with disease progression to accelerated- and blast-phase CML [ 8 ]. Furthermore, increased proportions of cytotoxic CD56 dim and memory-like CD57 NK cells are associated with successful TFR in CML patients after imatinib discontinuation [ 3 , 5 , 34 ].…”
Section: Leveraging the Immune System To Enhance Tfr: Targeting Specific Immune Functionsmentioning
confidence: 99%
“…The three best described checkpoint molecules—PD1, T-cell immunoglobulin and mucin domain 3 (TIM3), and cytotoxic T lymphocyte antigen 4 (CTLA-4), act as inhibitory receptors of T-cells and have been associated with immune evasion in CML. CML-specific CTLs were characterized by the high expression of PD1, whereas their target leukemic cells expressed higher levels of its ligand, PDL1, in a CML mouse model and in patients [ 9 , 12 , 34 ]. PD1/PDL1 interactions contribute to functional T-cell impairment, which fails to eliminate measurable residual disease and may be related to leukemia relapse.…”
Section: Leveraging the Immune System To Enhance Tfr: Targeting Specific Immune Functionsmentioning
confidence: 99%